Theoretical study on the load carrying capacity of concrete drilled and expanded piles with different stiffness under horizontal load. Issue 1 (April 2021) - Qian, Yongmei; Li, Mingxiao; Wang, Ruozhu; Jin, Yujie
Abstract: Concrete drilling and expanding pile is a new type of pile in the field of foundation engineering, which has been improved compared with the traditional straight-hole pile. The expansion technology improves the bearing capacity of the pile and it has great prospect for development as it changes the overall bearing capacity of the pile. Although the performance of expanded piles under vertical loads has been studied, the performance of expanded piles when subjected to horizontal loads is not fully understood. In order to study the performance of concrete expansion piles against horizontal loads, especially the overturning resistance of the overturned piles and bent piles, a numerical simulation study is conducted in this paper